Criminological characteristics of participants in organized crime (Journal of actual problems of jurisprudence, 2022)
This article is devoted to the issues of criminological characteristics of a participant in organized crime. The study of the personality of the offender is one of the central elements of the system of counteraction to a specific type of crime. The correct definition of the key criminological features of a criminal's personality is the basis for effective counteraction to criminal offenses committed by persons with these characteristics.In the article, the authors reveal the issues of classification of organized criminals, signs inherent in the main types of organized criminals, issues of sources of moral formation of the individual, the main features inherent in modern leaders of organized criminal associations.The authors believe that persons who carry out criminal activities on an ongoing basis as part of an organized criminal group pose an increased public danger to society. Moreover, in view of their inherent personality traits, it becomes possible for them to actively influence other members of society with their subsequent involvement in the organized crime system. In turn, the ideology of impunity and life "on a grand scale" spread by the leaders of organized criminal groups acts as a destructive element in the formation of the personality of minors.Key words: organized crime, personality, criminal, organized criminal group, criminological characteristics.